Experimental investigations and optimization of process parameters of meshed-wick heat pipe (International Journal of Food and Nutritional Sciences, 2019)
Heat pipes are used to transfer heat, which are hollow cylindrical shape device filled with small amount of working fluid, which can change its phase. The rate of heat transfer in heat pipes compared to normal heat exchanging devices is more. Depending on the applications of heat transfer various heat pipes are being designed. Methanol fluid is used with 50% fill ratio. It is made of copper with outer diameter of 15.88mm and inner diameter of 14.88mm. It consists of a screen mesh made of copper powder inside it with thickness of 0.5mm. Due to heat input methanol changes its phase from liquid to vapor. The vapor loses its heat and changes its phase back to liquid in the condenser. At the condenser section the vapour gives up it heat and changes its phase from vapour to liquid.